Genome-wide identification and expression analysis of the ADH gene family in Artemisia annua L. under UV-B stress - Pan, Hengyu; Shi, Peiqi; Zhong, Shan; Ding, Xiaoxia; Bao, Shengye; Zhao, Siyu; Chen, Jieting; Dai, Chunyan; Zhang, Danchun; Qiu, Xiaohui; Liao, Baosheng; Huang, Zhihai (Frontiers in Plant Science, 2025)
ADHs are key genes that catalyze the interconversion between alcohols and aldehydes, which play crucial roles in plant adaptation to a range of abiotic stresses. However, the characterization and evolutionary pathways of ADH genes in the antimalarial plant Artemisia annua are still unclear. This study identified 49 ADH genes in A. annua and conducted a detailed analysis of their structural features, conserved motifs, and duplication types, revealing that tandem and dispersed duplications are the primary mechanisms of gene expansion. Evolutionary analysis of ADH genes between A. annua (AanADH) and A. argyi (AarADH) revealed dynamic changes, with 35 genes identified deriving from their most recent common ancestor in both species. ADH1, crucial for artemisinin production, had two copies in both species, expanding via dispersed duplication in A. annua but whole-genome duplication in A. argyi. CREs and WGCNA analysis suggested that AanADH genes may be regulated by UV-B stress. Following short-term UV-B treatment, 16 DEGs were identified, including ADH1 (AanADH6 and AanADH7), and these genes were significantly downregulated after two hours treatment (UV2h) and upregulated after four hours treatment (UV4h). The expression changes of these genes were further confirmed by GO enrichment analysis and qRT-PCR experiments. Overall, this study comprehensively characterized the ADH gene family in A. annua and systematically identified AanADH genes that were responsive to UV-B stress, providing a foundation for further research on their roles in abiotic stress responses.